Temporal changes in Plasmodium falciparum genetic diversity and multiplicity of infection across three areas of varying malaria transmission intensities in Uganda - Alex Mwesigwa; Steven M. Kiwuwa; Benson Musinguzi; Hakiim Kawalya; James Davis Katumba; Andrew Baguma; Irene M. Mutuku; Ismail Abiola Adebayo; Samuel L. Nsobya; Pauline Byakika-Kibwika; Joan N. Kalyango; Charles Karamagi; et al. (Tropical Medicine and Health)
Abstract Background Malaria is a significant public health challenge in Uganda, with Plasmodium falciparum (P. falciparum) responsible for most of malaria infections. The high genetic diversity and multiplicity of infection (MOI) associated with P. falciparum complicate treatment and prevention efforts. This study investigated temporal changes in P. falciparum genetic diversity and MOI across three sites with varying malaria transmission intensities. Understanding these changes is essential for informing effective malaria control strategies for the different malaria transmission settings. Methods A total of 220 P. falciparum-positive dried blood spot (DBS) filter paper samples from participants in a study conducted during 2011–2012 and 2015–2016 were analyzed. Genotyping utilized seven polymorphic markers: Poly-α, TA1, TA109, PfPK2, 2490, C2M34–313, and C3M69–383. Genetic diversity metrics, including the number of alleles and expected heterozygosity, were calculated using GENALEX and ARLEQUIN software. MOI was assessed by counting distinct genotypes. Multi-locus linkage disequilibrium (LD) and genetic differentiation were evaluated using the standardized index of association (IA S) and Wright's fixation index (FST), respectively. Statistical comparisons were made using the Kruskal–Wallis test, and temporal trends were analyzed using the Jonckheere–Terpstra test, with statistical significance set at p < 0.05. Results Of the 220 samples, 180 were successfully amplified. The majority of participants were males (50.6%) and children aged 5–11 years (46.7%). Genetic diversity remained high, with mean expected heterozygosity (He) showing a slight decrease over time (range: 0.73–0.82). Polyclonal infections exceeded 50% at all sites, and mean MOI ranged from 1.7 to 2.2, with a significant reduction in Tororo (from 2.2 to 2.0, p = 0.03). Linkage disequilibrium showed a slight increase, with Kanungu exhibiting the lowest IA S in 2011–2012 (0.0085) and Jinja the highest (0.0239) in 2015–2016. Overall genetic differentiation remained low, with slight increases in pairwise FST values over time, notably between Jinja and Tororo (from 0.0145 to 0.0353). Conclusions This study highlights the genetic diversity and MOI of P. falciparum in Uganda's malaria transmission settings, noting a slight decrease in both genetic diversity and MOI overtime. Continued surveillance and targeted control strategies are essential for monitoring the impact of malaria control efforts in Uganda.